Control of Microcystis spp . Bloom By Combination of Indigenous Denitrifying Bacteria From Sutami Reservoir With Fimbristylis globulosa and Vetiveria zizanoides - Bayu Agung Prahardika; Catur Retnaningdyah; Suharjono - (Journal of Tropical Life Science, 2013)
The purpose of this research were to know the ability of polyculture macrophyte (Fimbristylis globulosa and Vetiveria zizanoides) and combination of both with consortium of indigenous denitrifying bacteria from Sutami reservoir that added by Microcystis spp. or not to reduce the concentration of nitrate, dissolved phosphate and the carrying capacity of Microcystis spp. Experiment was done in medium of Sutami reservoir water enriched with 16 ppm of nitrate and 0,4 ppm of phosphate. Denitrifying bacteria were used in this research were DR-14, DU-27-1, DU-30-1, DU-30-2, TA-8 and DU-27-4 isolated from Sutami reservoir. The treatments were incubated during 15 days. Microcystis spp. abundance was calculated every day, but measurement of the the concentration of nitrate and dissolved phosphate were done every six days. The results showed that both treatment and a combination of both macrophytes with a consortium of denitrifying indigenous bacteria were added or not either Microcystis able to reduce nitrate at 99% and 93-99% orthophosphoric. Combination of macrophytes with denitrifying indigenous bacterial consortium from Sutami reservoir was able to inhibit the carrying capacity of Microcystis spp. highest until 47.87%. They can also significantly reduce the abundance of Microcystis from 107 cells/mL in early of treatment to become 0.35x104 cells/mL after fifteen days incubation.